Evaluation of enhanced efficient fertilizer urea on rice production and environment - Hashim, Mohammad Mu'az (2016)
The use of enhanced efficiency fertilizer (EEF) urea as an alternative for the conventional urea fertilizer is one of the main strategies to improve nitrogen use efficiency (NUE) in rice cultivation. The production of affordable EEF with good quality could increase its consumption by farmers. The objectives of this study were to evaluate the efficiency of the selected urea EEF in enhancing NUE, reducing gaseous N emission and improving rice productivity. Three groups of EEF were used; biochar impregnated urea (BIU) comprising of BIU 300-5, BIU 300-10, BIU 700-5, and BIU 700-10; geopolymer coated urea (GCU) comprising of single layer geopolymer coating (UG1), double layer coating (UG2), and single layer starch-modified geopolymer (SG1); and palm stearin coated urea (PSCU) with inhibitors comprising of PS, PS+DMPP-50, PS+DMPP- 100, PS+DMPP-150, PS+Cu, and PS+Zn. Isotopic study using 15N was carried out to determine the timing of N uptake by rice as a guideline for EEF development. Rice removed N until 11th week after transplanting and the NUE was about 57% under common practices. Nitrogen derived from fertilizer (NDFF) were 22-40% in straw, 18.7-29.3% on root, and 26.4- 27.8% in grain. Laboratory study of the selected EEF was carried out to determine the N transformation, ammonia (NH3) volatilization loss and nitrous oxide (N2O) emission on Selangor soil and Chempaka soil. Both GCU and PSCU retained substantial amount of urea-N in soil after 2 weeks of application. Application of EEF resulted in higher N recovery after 4 weeks by 4.6-17.6%. The use of EEF also resulted in the reduction of NH3 loss as by 26-30% in BIU, 11-19% in GCU, and 16-35% in PSCU, while N2O emission was reduced by 15.0-49.8%. In a pot study under glasshouse condition, rice were planted with isotopic 15N was used to determine the fertilizer-N uptake by rice. The application of EEF resulted in yield increment by 19-106% in Selangor soil and 10-37% in Chempaka soil. The application of EEF also reduced ammonia volatilization loss by 31-77% on Selangor soil and 21-56% on Chempaka soil, while N2O emission flux was reduced by 52.7-100.0% on both soil series. Fertilizer-N uptake was improved by EEF treatments by 28-140%. A field trial was carried out in Sungai Besar to evaluate the efficacy of EEF on rice production and N uptake under field condition using BIU and PSCU EEF. Application of EEF had significantly improved height, SPAD values (chlorophyll content) and harvest index of rice plants. The EEF treatments also improved grain yield by 5-20% and N uptake by 12.2-35.6% compared to urea. In conclusion, EEF application improved NUE, reduced gaseous N emission and increased rice production compared to the conventional urea.